Cerebral Vascular Hamartoma In a Campeiro Bulldog - Barros, Rafaela Magalhães; Gulgemin, Gustavo Andrade; Barreto, Lucas Silva; de Souza Almeida, Ana Maria; Wilson, Tais Meziara; Machado, Mizael; Bittencourt, Alexandra Ariadne; de Castro, Márcio Botelho (Acta Scientiae Veterinariae, 2020)
Background: Vascular hamartomas (VH) are rare or simply underdiagnosed injuries in veterinary medicine and represent a non-neoplastic developmental anomaly disorganization and proliferation of endothelial tissue. VH occur in any region of the body, however in the brain present clinical relevance related with the potential for spontaneous bleeding, adjacent tissue compression and convulsive activity. The aim of these report is to describe clinical, pathological and immunohistochemical features of a case of cerebrovascular hamartoma and highlight the diagnosis of these rare brain disorder in dogs. Case: A 10-year-old male dog, a Campeiro Bulldog breed presented convulsions episodes and died before an elective surgical procedure for eyelid nodule removal. Three red nodules were observed in the brain, one between the parietal lobe and the left occipital lobe (in the medium suprasylviam sulcus), the other in the caudal region of the corpus callosum and the third one in the cerebellar cortex. Central nervous system, eyelids and most organs and tissues samples were collected, fixed in 10% formaldehyde and processed for histopathological analysis. Histologically, in the eyelid was detected a sebaceous adenoma. The nervous system samples revealed well-differentiated different sizes vascular structures with thin-walled and blood-filled, promoting compression of the brain. Normal neuropile was detected between the vascular structures substantiating cerebral vascular hamartoma diagnosis in the dog. Immunohistochemical assay was conducted with CD31 (monoclonal mouse antibody anti-CD31, Clone JC70A, Dako Corp.) and Von Willebrand factor (monoclonal mouse antibody anti-Von Willebrand factor, Clone F8/86, Dako Corp.) using the biotin–peroxidase–streptavidin method (PolyDetector Plus DAB–HRP, Bio SB) on CNS sections to confirm the vascular origin of the lining cells in the mass. Discussion: Hamartomas are rarely reported in domestic animals and mostly are of vascular origin. VH in nervous tissues can trigger clinical signs related to hemorrhage, brain space occupation, compression and obstructive secondary hydrocephalus. In general, cerebral VH have a slow progression and usually affected animals are asymptomatic. On the other hand, cerebral vascular hamartomas may also cause clinical signs in very young animals about 15 to 16 months old. In humans, clinical presentation of VH may be related with acquired lesions such as trauma, ionizing radiation, and other central nervous system injuries. In the present case, the dog presented convulsion episode only at 10 years old during pre-chirurgical procedures. The morphological features of the vascular hamartoma we observed in the Campeiro bulldog is classified as capillary teleangiectasia composed by well differentiated capillaries lined with well differentiated endothelial cells interspaced by normal neuronal tissue. Histopathological and immunohistochemical assay are extremely important to differentiate hamartoma from other tumors, since they may be macroscopically similar. The immunolabeling of endotelial cells by anti-CD31 and anti-Von Willebrand factor antibodies in the cerebral VH, highlight the vascular origin of the masses detected. However, it is also important to perform systematic gross examination of the brain in detail to detect even the smallest injuries in asymptomatic animals avoiding underdiagnoses of cerebral VH.